2022
DOI: 10.1186/s43088-022-00196-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and pharmacological aspects of piperine as a potential molecule for disease prevention and management: evidence from clinical trials

Abstract: Background Piperine is a type of amide alkaloid that exhibits pleiotropic properties like antioxidant, anticancer, anti-inflammatory, antihypertensive, hepatoprotective, neuroprotective and enhancing bioavailability and fertility-related activities. Piperine has the ability to alter gastrointestinal disorders, drug-metabolizing enzymes, and bioavailability of several drugs. The present review explores the available clinical and preclinical data, nanoformulations, extraction process, structure–a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 187 publications
0
36
0
Order By: Relevance
“…In addition, PPN is considered to be the first and most potent natural bioenhancer [ 8 ]. PPN has significant potential to inhibit CYP3A4 (a metabolizing enzyme) and P-glycoprotein (P-gp; an efflux transporter) [ 9 , 10 ]. P-gp is basically an efflux transporter that effluxes several drugs out of the cells after absorption from the intestine [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PPN is considered to be the first and most potent natural bioenhancer [ 8 ]. PPN has significant potential to inhibit CYP3A4 (a metabolizing enzyme) and P-glycoprotein (P-gp; an efflux transporter) [ 9 , 10 ]. P-gp is basically an efflux transporter that effluxes several drugs out of the cells after absorption from the intestine [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This structural feature leads to characteristic ultraviolet (UV) absorptions [ 20 ]. A review reported in the literature this year (2022) gathered a set of studies of important targets that interact (experimental and computational results) with piperine [ 21 ]. This set of proteins is composed by inflammatory cytokines (IL-8, IL-10, IL-1 h, IL-6), transcriptional factors (AP-1, NF-κB, ATF-2), kinases (JNK, ERK1, ERK2, Akt, P38 MAPK), enzymes (NOS-2, COX-2, MMP-2, MMP-9), transporter genes (CYP3A4, RV1258c, MRP1, BCRP), and cell-cycle proteins (cyclin A/D/T, CDK-2, CDK-4), among others.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological significance of the metabolites present in DSV, particularly their anti-inflammatory properties, are well documented ( Semaming et al, 2015 ; Semwal et al, 2015 ; Correa et al, 2016 ; Graebin, 2018 ; Rios et al, 2018 ; Kahkeshani et al, 2019 ; Ruwizhi and Aderibigbe, 2020 ; Li C.-X. et al, 2021 ; Nisar et al, 2021 ; Sharifi-Rad et al, 2021 ; Tripathi et al, 2022 ). Recently, DSV has also been reported to ameliorate S protein-induced inflammatory response in A549 xenotransplanted zebrafish by reducing IL-6 and TNF-α, pro-inflammatory cytokine levels and rescuing fever-driven swimming behavioural patterns ( Balkrishna et al, 2020c ).…”
Section: Introductionmentioning
confidence: 99%